Strategies For Primary School Students Understanding Of Character Education Through The Active Role Of Teachers - Laros Tuhuteru; Emy Yunita Rahma Pratiwi; Tri Suryowidiyanti; Devin Mahendika; Dahlan Abdullah (Journal on Education, 2023)
Character education plays a vital role in the development of children's mature personalities. The lack of adequate character education strengthening in schools is an issue that requires attention. As facilitators, companions, and sources in the process of conveying knowledge to students about the importance of character education in elementary school, teachers must play a crucial role in the development of children's character. This study aims to analyze the role of teachers in assisting elementary schools in implementing strategies for improving elementary school students' understanding of character education in order to provide benefits in terms of understanding the obstacles in the application of character education in elementary schools and strategies that can be implemented, particularly for teacher-student communication. Using a literature review, this study determines the elements and tactics that can be implemented in primary schools to improve character education for pupils. Recommendations were made for schools based on the findings, including employing active learning techniques and incorporating character education values into all learning materials. Reflection and evaluation should also be conducted to assist students in comprehending and improving their character education-related behavior. To reach the true aims of character education, it is necessary to overcome obstacles such as schools' lack of preparedness, educators' lack of comprehension, and ineffective learning techniques.